FROM CLICKS TO ANALYTICS: THE PROMOTION OF CRITICAL-CREATIVE THINKING THROUGH TEALL INTEGRATION - Mayuni, Ilza; Ratminingsih, Ni Made; Zaim, Muhammad; Halim, Nurhasanah; Chen, Yinghuei; Palupi, Tara Mustikaning (LPPM Universitas Jambi, 2026)
The promotion of critical and creative thinking through technology integration at once in English learning presents a large challenge. This study employs a qualitative approach to explore teachers’ viewpoints of promoting students’ critical and creative thinking through Technology-enhanced Active Language Learning; and the extent of teachers integrating TEALL into English learning at Junior High School (JHS) in Indonesia. Employing qualitative approach with purposive sampling, eight junior high school teachers from three islands of Indonesia were recruited. Research data were transcriptions of recorded interviews, teacher reflective journals, and Google Search Console (GSC) performance report. Triangulation was used to compare and cross-check findings and increase research credibility and validity. Findings show teachers emphasize the promotion of critical and creative thinking based on cognitive processes, linking critical thinking to receptive skills and creative thinking to productive skills. TEALL integration is viewed as supportive instead of transformative to the promotion. Such evidences as lengthy texts and complex sentences are considered the best input to facilitate students’ critical analysis. The view stems from teachers’ apprehension of evident infusion of critical and creative thinking into the instructions. The key to success of integrating TEALL is teachers’ acceptance. Increasing teachers’ self confidence and commitment can be the driving force underlying the learning outcomes. Strengthening their readiness can also be the lever for impactful practices. This study is limited by the diverse social and cultural differences present in Indonesia. Therefore, future research in education reform should take these as essential aspects and decide their position within.